Waktu Reproduksi Karang Lunak Sinularia flexibilis Quoy & Gaimard (Octocorallia: Alcyonacea) Di Pulau Barrang Lompo, Kepulauan Spermonde, Sulawesi Selatan - Abdul Haris (Universitas Atma Jaya Yogyakarta, 2010)
Sinularia flexibilis is a soft coral that has an economical value due to its farmacological substance. The aim of this research was to find out the spawning time and behaviour of Sinularia flexibilis by visual observation in its natural habitat and in hatchery. The result of this research revealed that the reproduction period of the Sinularia flexibilis occurred during May to September in each lunar phase. However, it was found that during a new moon phase, the reproduction activity had the highest percentage of colony for every lunar phase. Spawning behavior of the Sinularia flexibilis was that a bunch of eggs and the sperm were separately spawned from the mouth by fast contraction in a short period of time.